Respective roles of social deprivation, health literacy, and clinical factors for COVID-19: a case-control study in hospitalized patients - Dahmane, Lotfi; Julia, Chantal; Vignier, Nicolas; Sesé, Lucile; Brichler, Ségolène; Benaïnous, Ruben; Bihan, Hélène; Lopez-Sublet, Marilucy; Trawale, Damien; Bouchaud, Olivier; Goupil de Bouillé, Jeanne; , on behalf of the SOCIALCOV group (Frontiers in Public Health, 2023)
Introduction: To investigate the association between social deprivation and COVID-19 among hospitalized patients in an underprivileged department of the greater Paris area. Methods: Individuals hospitalized for COVID-19 between March 1 st and October 31, 2020, were included, matched on age and sex, and compared with patients hospitalized for any other reason with negative RT-PCR for SARS-CoV-2, through a case-control study. Clinical, sociodemographic characteristics, health literacy, and social deprivation, assessed by the EPICES score, were collected. Factors associated with COVID-19 in hospitalized patients were assessed using univariate and multivariate logistic regression models. Results: 69 cases and 180 controls were included. Participants were mostly men (N = 148: 59.4%) aged 65 or older (N = 109: 44.1%). Median EPICES score was 43.2 (IQR 29.4 -62.9). EPICES score > 30.17(precariousness threshold) was not significantly associated with COVID-19 in hospitalized patients (adjusted odds ratio (aOR) = 0.46; 95% Confidence Interval (CI) [0.21-1.01]). EPICES score > 30.17 (precariousness threshold) was not significantly associated with COVID-19 (aOR = 0.46; 95% CI [0.21; 1.01]). Advanced age, higher BMI, professional activity, home area of less than 25 m 2 per person, and low health literacy, were significantly associated with COVID-19 in hospitalized patients. Discussion: This study highlights probable risk factors for specific exposition in disadvantaged area: maintenance of professional activity, smaller home area, and low health literacy.